2022
DOI: 10.3390/ph15020244
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Phloridzin and Other Phenolic Compounds in Apple Tree Leaves, Bark, and Buds Using Liquid Chromatography with Multilayered Column Technology and Evaluation of the Total Antioxidant Activity

Abstract: Apples are known to be a rich source of phenolic compounds, however detailed studies about their content in the individual parts of apple trees are reported rarely. For this purpose, we tested various stationary phases for the determination of phenolic compounds in leaves, bark, and buds. Phloridzin, phloretin, chlorogenic acid, rutin, and quercitrin were analyzed with high performance liquid chromatography coupled with diode array detection. A YMC Triart C18-ExRS 150 × 4.6 mm, 5 µm particle size analytical co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Moreover, it should be made clear that most electrochemical techniques provide the information regarding the total antioxidant capacity (TAC) values of the antioxidants, which represents the cumulative impact of all the antioxidants present in the sample in contrast to the determination of the individual antioxidant potentials measured via a parameter of AOC. Electrochemical techniques involved in evaluating the antioxidant potential of biogenic samples are discussed in detail in the subsection [ 44 ].…”
Section: Electrochemical Methodologiesmentioning
confidence: 99%
“…Moreover, it should be made clear that most electrochemical techniques provide the information regarding the total antioxidant capacity (TAC) values of the antioxidants, which represents the cumulative impact of all the antioxidants present in the sample in contrast to the determination of the individual antioxidant potentials measured via a parameter of AOC. Electrochemical techniques involved in evaluating the antioxidant potential of biogenic samples are discussed in detail in the subsection [ 44 ].…”
Section: Electrochemical Methodologiesmentioning
confidence: 99%
“…Findings from alternative studies suggest that the contribution of abiotic factors, such as the accumulation of phenolic detritus from previous orchard plantings, may play a role in apple replant disease development as well. Phloridzin represents one of the most abundant phenolic compounds found in apple roots ( Emmett et al, 2014 ; Nicola et al, 2016 ), leaves, bark, and buds ( Adamcová et al, 2022 ). Emmett et al (2014) found that the quantity of phloridzin increases with root order and may reach concentrations of > 10% root dry weight in higher order roots (3rd and 4th order).…”
Section: The Case Against the Build-up Of Phenolic Compounds In Soilmentioning
confidence: 99%
“…Several reports revealed that the plant material of apple trees is a rich source of phenolic compounds [1,3,[5][6][7][8][9][10][11][12][13]. For instance, Adamcová et al [5] reported high values of phenolic compounds in leaf extracts from thirteen cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports revealed that the plant material of apple trees is a rich source of phenolic compounds [1,3,[5][6][7][8][9][10][11][12][13]. For instance, Adamcová et al [5] reported high values of phenolic compounds in leaf extracts from thirteen cultivars. In extracts, the content of phenolic compounds was in the range of 54.68-106.81 mg/g of dried weight (DW), while phloridzin was found as a major component and had a concentration range of 46.43-98.51 mg/g DW [5].…”
Section: Introductionmentioning
confidence: 99%